Respuesta :

x = [tex]\frac{3}{2}[/tex] ± [tex]\frac{1}{2}[/tex]i

rearrange the equation and equate to zero

2x² - 6x = - 5 ⇒ 2x² - 6x + 5 = 0

this doesn't factor with integers, hence use the quadratic formula to solve

with a = 2, b = - 6 and c = 5

x = (6 ± √(36 - 40 ) )/4

  = (6 ± √(-4) ) / 4

  = (6 ± 2i ) / 4

x = [tex]\frac{3}{2}[/tex] ± [tex]\frac{1}{2}[/tex]i



x =  ± i


rearrange the equation and equate to zero


2x² - 6x = - 5 ⇒ 2x² - 6x + 5 = 0


this doesn't factor with integers, hence use the quadratic formula to solve


with a = 2, b = - 6 and c = 5


x = (6 ± √(36 - 40 ) )/4


  = (6 ± √(-4) ) / 4


  = (6 ± 2i ) / 4


x =  ± i


Read more on Brainly.com - https://brainly.com/question/11557783#readmore